2016
DOI: 10.3109/14756366.2016.1151015
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and anti-inflammatory activity evaluation of novel triazolyl-isatin hybrids

Abstract: New isatin-triazole based hybrids have been synthesized and evaluated for their inhibitory activity of TNF-a induced expression of Intercellular Adhesion Molecule-1 (ICAM-1) on the surface of human endothelial cells. Structure-activity relationship (SAR) studies revealed that the presence of the electron-attracting bromo substituent at position-5 of the isatin moiety played an important role in enhancing the anti-inflammatory potential of the synthesized compounds. Z-1-[3-(1H-1,2,4-Triazol-1-yl)propyl]-5-bromo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(26 citation statements)
references
References 38 publications
(46 reference statements)
0
24
0
2
Order By: Relevance
“…Isatin has emerged as a promising nucleus and attracted increasing attention in medicinal chemistry and drug discovery over the past decade [ 10 ]. Previous literature reports indicated that isatin and its derivatives have diverse types of biological activity, including anticancer [ 11 ], antibacterial [ 12 ], antiviral [ 13 ], anticonvulsant [ 14 ], anti-inflammatory [ 15 ], and antifungal activity [ 16 ]. Notably, some isatin derivatives have been approved for clinic use such as sunitinib, toceranib, and nintedanib.…”
Section: Introductionmentioning
confidence: 99%
“…Isatin has emerged as a promising nucleus and attracted increasing attention in medicinal chemistry and drug discovery over the past decade [ 10 ]. Previous literature reports indicated that isatin and its derivatives have diverse types of biological activity, including anticancer [ 11 ], antibacterial [ 12 ], antiviral [ 13 ], anticonvulsant [ 14 ], anti-inflammatory [ 15 ], and antifungal activity [ 16 ]. Notably, some isatin derivatives have been approved for clinic use such as sunitinib, toceranib, and nintedanib.…”
Section: Introductionmentioning
confidence: 99%
“…[19,20] Huisgen's 1,3-dipolar cycloaddition reaction between terminal alkynes and azides has attracted interest in medicinal chemistry. [21] These classes of heterocyclic moiety and 1,2,3triazole possesses various biological and pharmacological properties, such as anti-cancer, [22] anti-tubercular, [23] anticonvulsant, [24] anti-viral, [25] cytotoxicity, [26] anti-bacterial, [27] antiinflammatory, [28] anti-oxidant [29] and it is due to lipophilicity, polarity and hydrogen bonding of molecules which consequently improves the pharmacological, pharmacokinetic, toxicological, and physicochemical properties of drug candidates. [30] Perceptibly, isatin and 1,2,3-triazole derivatives occupy an important position in the development of new drugs.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 2,3-Dioxindole (isatin, I, Figure 1) is a natural substance found in some plant species, which can also be present in humans, due to endogenous consumption. Compound I has a distinguished pharmacological profile and exhibits a wide spectrum of biological actions, including anti-oxidant, 7 anti-inflammatory, 8 antibacterial, 9 and anticancer 10,11 activities. The United States Federal Drug Administration approved sunitinib and nintedanib as isatin-bearing anticancer drugs, 10,12 and many compounds with an isatin scaffold such as SU6668 and SU5416 have displayed outstanding anticancer activity.…”
Section: Introductionmentioning
confidence: 99%